DINAMIKA KEWIRAUSAHAAN PEREMPUAN MUDA DALAM MENGELOLA BISNIS : STUDI KASUS UMKM DI SEMARANG - Masine Slahanti; Novianto Noegroho; Johanis Souisa; Soegihartono Soegihartono (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study aims to explore the entrepreneurial dynamics of young women in managing snack and catering businesses within the Micro, Small, and Medium Enterprises (MSMEs) sector in Semarang. The research focuses on motivation, challenges, adaptive strategies, and business sustainability orientationMethods: A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, participatory observation, and documentation involving young women entrepreneurs. Data validity was ensured through source and method triangulation.Results: The findings reveal that entrepreneurial motivation among young women is driven not only by economic necessity but also by self-actualization and the need for flexibility in balancing domestic and productive roles. The main challenges include limited access to capital, low digital literacy, and intense market competition. In response, entrepreneurs adopt adaptive strategies such as product innovation, digital-based marketing optimization, and strengthening social and customer networks. Furthermore, the study identifies strong resilience and adaptive capacity as key social capital in sustaining business continuity.This study contributes to the literature by uncovering the entrepreneurial dynamics of young women as an adaptive process shaped not only by economic factors, but also by the interplay of dual roles, resilience, and adaptive strategies in navigating constraints and a changing business environment. These findings highlight the importance of strengthening young women’s entrepreneurial capacity through training, access to financing, and community-based mentoring to enhance the competitiveness and sustainability of MSMEs at the local level. Keywords: Young Women Entrepreneurship, MSMES, Adaptive Strategies, Resilience, Business Sustainability